Integration of 3D Scanning and Augmented Reality (AR) Technology in East Kalimantan Furniture Products in E-Commerce - Syaputra, Eko Agung; Mujahidin, Syamsul; Sartika, Widya; Rossalina, Novianti (VCD: Journal of Visual Communication Design, 2023)
The creative furniture industry in East Kalimantan faces the challenge of less effective online marketing in e-commerce. In 2018, there were more than 370 furniture entrepreneurs in the region, but only 37% of their total production managed to reach the market. According to projections from Markets and Markets, the market value of Augmented Reality (AR) in e-commerce is expected to grow by 34% between 2020 and 2025. To overcome this problem, the use of 3D object configuration visual technology and AR presents a better solution. promising solution. This technology can improve product presentation, create a more interactive and realistic shopping experience, and reduce the environmental impact of e-commerce due to the re-shipment of non-conforming products. The main objective of the research is to assess the effectiveness of product communication, the ease of the purchasing process, and the level of consumer trust in the product. This visual method of 3D object configuration combines 3D scanning to produce detailed and realistic 3D images. This research uses a sprint design method based on design thinking, which involves co-creation to refine ideas. Next, a prototype design was developed with a focus on aspects of the user interface and user experience, fostering intelligent interaction between users and their environment, thus contributing to the progress of the Smart City concept in IKN Nusantara.